2015
DOI: 10.1074/jbc.m114.605998
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid-binding Proteins 1 and 2 Differentially Modulate the Activation of Peroxisome Proliferator-activated Receptor α in a Ligand-selective Manner

Abstract: Background: Fatty acid-binding proteins (FABPs) chaperone intracellular transport of lipophilic ligands. Results: FABP1 and FABP2 differentially promote drug activation of peroxisome proliferator-activated receptor ␣ (PPAR␣) via ligand-dependent protein-protein interactions. Conclusion: Drug activation of PPAR␣ is regulated by the presence of different FABPs. Significance: FABPs may act in a tissue-specific manner to enhance the selectivity of PPAR␣ agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
63
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 33 publications
9
63
0
3
Order By: Relevance
“…It is also possible that drug binding to FABPs may have a more profound impact on drug trafficking to intracellular organelles such as the nucleus, rather than overall drug transport. This has been shown previously for drug binding to FABP1 and FABP2 (44) and FABP4 (44,45). This may govern access to eg.…”
Section: Discussionsupporting
confidence: 62%
“…It is also possible that drug binding to FABPs may have a more profound impact on drug trafficking to intracellular organelles such as the nucleus, rather than overall drug transport. This has been shown previously for drug binding to FABP1 and FABP2 (44) and FABP4 (44,45). This may govern access to eg.…”
Section: Discussionsupporting
confidence: 62%
“…Similarly, 2 different FABPs may enhance activity of PPARγ or PPARβδ (46). Mechanistically, FABP1 and FABP2 were reported to enhance PPARα transcriptional activity by translocating from the cytoplasm to the nucleus in a ligand-dependent manner, presumably to deliver ligand to the PPARα transcriptional complex (47). Therefore, it becomes attractive to hypothesize that RBP7 might regulate the transcriptional activity of certain PPARγ target genes such as AdipoQ in the endothelium by a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The fi ndings demonstrated that oleic acid was the only FA tested able to fully abolish the binding of BODIPY-FLC 12 to zebrafi sh Fabp1b.1. This is interesting, as oleate binding causes a conformational change in rat FABP1 ( 76 ) and increases the nuclear localization of FABP1 and FABP2 ( 23,33 ). Oleic acid may be involved in the transcriptional regulation of gene expression ( 77,78 ), and the presence of either FABP1 or FABP2 magnifi es the transcriptional activation mediated by PPAR ␣ ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated, using cell cultures, that FABPs may channel unesterifi ed FAs and other lipophilic ligands into nuclei, potentially targeting them to transcription factors, and initiate nuclear receptor transcriptional activity ( 11,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). To our knowledge, no in vivo data are currently available to support the hypothesis that exogenous FAs enter cell nuclei via their binding to FABPs.…”
Section: Extraction Of Total Rna Reverse Transcription and Pcr Analmentioning
confidence: 99%